TERANG DAN KEGELAPAN: PERAN PENDIDIKAN AGAMA KRISTEN MENUNTUN GENERASI ALPHA BERDASARKAN MAZMUR 119:105 - Yafarman Zai; Salmon Wompere (STT IKSM SANTOSA ASIH, 2025)
Generation Alpha is a generation group born and developed amidst the rapid advancement of the digital world, where technological developments, globalization, and information flow very quickly. This situation makes this generation superior in mastering technology, but at the same time faces them with serious challenges, such as moral and spiritual crises, and loss of identity. This study aims to describe the role of Christian Religious Education (PAK) in guiding Generation Alpha to live under the light of God's word as stated in Psalm 119:105,